Experimental evidence that cuckoos choose host nests following an egg matching strategy. Issue 1993 (22nd February 2023) - Zhang, Jinggang; Santema, Peter; Lin, Zixuan; Yang, Lixing; Liu, Meijun; Li, Jianqiang; Deng, Wenhong; Kempenaers, Bart
Abstract : The arms race between brood parasites and their hosts provides a classic model to study coevolution. Hosts often reject the parasitic egg, and brood parasites should therefore select host nests in which the colour of the eggs best matches that of their own. Although this hypothesis has received some support, direct experimental evidence is still lacking. Here, we report on a study of Daurian redstarts, which show a distinct egg-colour dimorphism, with females laying either blue or pink eggs. Redstarts are often parasitized by common cuckoos, which lay light blue eggs. First, we showed that cuckoo eggs were more similar in spectral reflectance to the blue than to the pink redstart egg morph. Second, we report that the natural parasitism rate was higher in blue than in pink host clutches. Third, we performed a field experiment in which we presented a dummy clutch of each colour morph adjacent to active redstart nests. In this set-up, cuckoos almost always chose to parasitize a blue clutch. Our results demonstrate that cuckoos actively choose redstart nests in which the egg colour matches the colour of their own eggs. Our study thus provides direct experimental evidence in support of the egg matching hypothesis.